Resuscitation with Intact Placental Circulation in a Preterm Infant with Hydrops Fetalis - Pratesi, Simone; Corsini, Iuri; Coviello, Caterina; Perugi, Silvia; Dani, Carlo (American Journal of Perinatology Reports, 2017)
A preterm infant with prenatal diagnosis of hydrops fetalis was spontaneously delivered at 30 weeks of gestational age in a tertiary level hospital. Prenatal echography pointed out severe bilateral pleural effusions and diffused subcutaneous edema. A neonatologist team, alerted at the expulsion stage of labor, assisted the neonate immediately after birth and bilateral hydrothorax was drained with intact placental circulation to avoid a nonrespiratory period and its possible detrimental hemodynamic effects. The newborn was well stabilized in the delivery room before cutting the umbilical cord and starting mechanical ventilation. Unfortunately, our patient died due to refractory respiratory failure on the fourth day of life. However, the intact placental circulation procedure was performed without adverse effects to the infant and might represent a promising option in addition to other resuscitation procedures for the management of this type of patient.
Keywords: hydrops fetalis; neonatal resuscitation; delayed cord clamping; bedside resuscitation